Organic acids as extractors of phytoavailable heavy metals in soils treated with sewage sludge - Pires, Adriana Marlene Moreno; Mattiazzo, Maria Emília; Berton, Ronaldo Severiano (Pesquisa Agropecuaria Brasileira, 2004)
An efficient extraction method to estimate concentrations of phytoavailable heavy metals has not been established yet, because the extractors used do not simulate reactions close to the roots. The objective of this work was to evaluate the use of a rhizospheric acid organic solution as an extractor of phytoavailable heavy metal from soils (Oxisols) treated with sewage sludge. Three Oxisols with different textures cultivated with banana, peach palm and coffee were studied. The extractor (solution composed by acetic, citric, lactic and oxalic acids with concentrations of 1.00, 0.72, 0.49 and 0.12 mol L-1, respectively) evaluation was performed from correlation analyzes between heavy metals (Cd, Cr, Cu, Ni, Pb e Zn) concentrations extracted from the soil, and plant tissue concentrations. The correlation was significant, indicating the extractant efficiency in all studied cases. Comparing the studied elements, the Pb amount extracted correlated better with its phytoavailability on the three situations investigated.